014 Long-term effectiveness of natalizumab for RRMS: UK and global interim results from TYSABRI observational program. Issue 6 (27th May 2022) - Nicholas, Richard; Harrower, Timothy; Su, Ray; Licata, Stephanie; Vonsy, Jean
Abstract : Introduction: The TYSABRI Observational Program (TOP) is a large, ongoing observational study in relapsing- remitting multiple sclerosis (RRMS) patients treated with natalizumab. Country-specific data on relapse and disability outcomes, alongside global data, can provide information on natalizumab's effectiveness in local practice. Methods: Annualised relapse rate (ARR) and cumulative probability of 24-week confirmed disability worsening (CDW; increase in Expanded Disability Status Scale [EDSS] score ≥1.5 from a baseline of 0.0, ≥1.0 from a baseline between 1.0–5.5, or ≥0.5 from a baseline of ≥6.0) and improvement (CDI; decrease ≥1.0 from a baseline EDSS score ≥2.0) were analysed in TOP UK (n=134) and global (N=6295) cohorts using data from July 2007 to November 2018. Updated data (as of November 2019) will be presented. Results: ARR decreased in UK patients from 2.21 in the year before initiation to 0.19 on natalizumab (P<0.0001), consistent with a global decrease from 2.00 to 0.21 (P<0.0001). At 7 years, probabilities of CDW and CDI were, respectively, 26.2% and 35.3% in UK patients and 27.9% and 32.1% globally. Conclusions: These TOP UK results show disease control that is generally consistent with global TOP results, supporting natalizumab's long-term effectiveness in real-world settings. Support: Biogen. Disclosures: Included on the poster. richard.nicholas@btinternet.com